“Makan Bergizi Gratis” Program Policy in Media Framing: A Study of iNews.id - Affandi, Ahmad Fahrul Muchtar; Ramdani, Alwan Husni (Universitas Telkom, 2025)
This study aims to analyze how iNews.id frames the Free Nutritious Meal Program (MBG) using Murray Edelman’s framing approach. MBG is one of the national priority programs launched after the 2024 general election, aiming to improve the nutritional quality of schoolchildren. The research adopts a constructivist paradigm and a qualitative approach, analyzing nine news articles published between December 2024 and January 2025. Data were analyzed based on Edelman’s three framing dimensions: categorization, rubrification, and ideological category. The findings show that, in the categorization dimension, iNews.id consistently frames MBG within an affirmative narrative, highlighting technical preparedness, community participation, and direct benefits for families. In the rubrification dimension, the news articles are distributed across the National, Lifestyle, Health, and Bulletin sections, broadening the issue’s context from state policy to everyday life. In the ideological category dimension, the framing positions the government as a protector and supporter of public welfare, asserts moral legitimacy, and minimizes potential conflicts through narratives of central-local harmony and clarification of sensitive issues. The study concludes that the framing constructed by iNews.id tends to reinforce a positive image of the government regarding MBG and minimize critical narratives. The limitation of this research lies in its focus on a single media outlet and a short period of analysis. Future research will involve a comparative study with other media owned by political practitioners to examine the influence of ownership affiliation on public policy framing patterns.Keywords: framing, online media, media ideology, Makan Bergizi Gratis, Indonesia’s media